SAT0366 GENDER DIFFERENCES IN PSORIATIC ARTHRITIS – IMPACT ON TUMOR NECROSIS FACTOR INHIBITORS PERSISTENCE AND RESPONSE. (June 2019) - Vieira-Sousa, Elsa; Eusébio, Mónica; Ávila-Ribeiro, Pedro; Khmelinskii, Nikita; Cruz-Machado, Ana Rita; Martins-Rocha, Teresa; Bernardes, Miguel; Faria, Daniela; Silva, Joana; Santos, Helena; Miguel, Claudia; Carvalho, Pedro; et al.
Abstract : Background: The impact of gender on tumor necrosis factor inhibitors (TNFi) effectiveness has been poorly studied in Psoriatic Arthritis (PsA) patients. Objectives: To study gender differences in persistence and response of 1 st TNFi in PsA patients. Methods: PsA patients prospectively followed at the Rheumatic Diseases Portuguese Registry (Reuma.pt), treated with a 1 st TNFi, between 2001 and 2016. Drug retention assessed by Kaplan-Meier survival analysis and Cox models, adjusted for the year of starting a TNFi. Response rates measured by EULAR response, DAPSA remission, MDA and ASDAS response, applying LUNDEX method, were compared between genders. Baseline predictors of discontinuation and response were identified (Cox and logistic regression models). Results: 750 PsA patients, mean age 47.6 (± 11.6) years and 50.3% (n=377) females. PsA females showed significantly different baseline PsA disease characteristics in comparison with males and had more severe peripheral disease activity (Table 1 ). The overall TNFi survival rate for females was also significantly lower when compared with males (Figure 1 ). Additionally, females experienced lower rates of response at 3 and 6 months (Figure 2 ). Female gender was further identified as an independent predictor factor of worse persistence and showed a lower chance of good EULAR response. Conclusion: PsA females from Reuma.pt have distinct PsA features and worse persistence and response to a 1 st TNFi in comparison with males. This might be related to gender dependent inflammatory pathways and was independent of baseline disease activity. Disclosure of Interests: Elsa Vieira-Sousa Grant/research support from: MSD, Novartis, Mónica Eusébio: None declared, Pedro Ávila-Ribeiro: None declared, Nikita Khmelinskii: None declared, Ana Rita Cruz-Machado: None declared, Teresa Martins-Rocha: None declared, Miguel Bernardes: None declared, Daniela Faria: None declared, Joana Silva: None declared, Helena Santos: None declared, Claudia Miguel: None declared, Pedro Carvalho: None declared, Tiago Costa: None declared, Lídia Teixeira: None declared, Tiago Meirinhos: None declared, Patrícia Nero: None declared, Joao Eurico Fonseca: None declared, Maria Jose Santos: None declared